Pengaruh Kompensasi Terhadap Produktivitas Kerja Karyawan Pada PT. Socfin Indonesia Kebun Aek Loba - Harnita, Rizki; Ramadhani, Sri (LPPM Universitas Labuhanbatu, 2022)
The purpose of this study was to determine the effect of compensation on employee productivity at PT. SOCFIN INDONESIA Aek Loba Plantation and to find out the variables that have a dominant influence on employee productivity. The theoretical basis used is human resource management using Multiple Linear Regression Analysis Tool. Based on the results of the engraving, the key to this research is Y = 0.790 + 0.480 X1 + 0.187 X2, meaning that the direct compensation variable (X1) is employee productivity. The correlation value (R) of 0.679 means that there is a strong relationship between the independent variables (X1 and X2) on the dependent variable (Y). While the coefficient of determination (R2) of 0.462 means that the direct compensation and indirect compensation variables have an influence of 46.2% on work productivity. From the f test, it is obtained that fcount 16,287 > ftable 3.24, meaning that the first hypothesis has a significant effect between direct compensation (X1) and indirect compensation (X2) on employee work productivity (Y) received. Meanwhile, the direct compensation t-test variable has a dominant influence on the beta value of 0.551 and the calculation of tcount 3.801 > ttable 2.02 with a significance value of 0.001 <0.05, the second hypothesis is accepted.